Revisiting the Portability of Performance Paradox: Employee Mobility and the Utilization of Human and Social Capital Resources - Raffiee, Joseph; Byun, Heejung (Academy of Management Journal, 2020)
This study revisits the portability of performance paradox—the common finding that external hires fail to replicate prior performance after switching firms—by examining how the nature of an employee’s human capital and social capital resources relate to the ease with which external hires can be utilized in an organization’s value creating activities. Drawing theoretically from the person–organization fit and social capital literatures, we theorize that the integration and utilization of external hires will correlate with two types of human capital resource fit: similarity and complementarity, and two dimensions of retained social capital resources: internal and external. Using data from the U.S. lobbying industry and novel empirical estimates of worker–firm fit, we provide descriptive evidence that employee utilization (performance) decreases post-mobility, consistent with the portability paradox. However, this relationship attenuates—in magnitude and duration—when there is human capital resource complementarity (but not similarity) between the employee and hiring firm or when the employee transfers social capital resources (internal or external). We also find some evidence that human capital and social capital function as substitutes, and post hoc analyses suggest the characteristics of human and social capital which facilitate the utilization of external hires also correlate with hiring firm performance.